2016
DOI: 10.1016/j.ienj.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Momentary fitting in a fluid environment: A grounded theory of triage nurse decision making

Abstract: Triage RNs require appropriately designed triage environments and computer technology that enable them to secure real time knowledge of the ED to maintain situation awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 119 publications
(527 reference statements)
1
31
0
3
Order By: Relevance
“…This shortcoming calls for providing educational trainings courses in the field of triage at the time of disasters for different hospital staff in Iran, especially those working in the emergency departments. In Reay et al study [22], emergency department nurses in Canada had high triage decision making, while in Tzeng et al study [23], majority of hospital nurses in Taiwan demonstrated poor readiness for disaster responses.…”
Section: Discussionmentioning
confidence: 97%
“…This shortcoming calls for providing educational trainings courses in the field of triage at the time of disasters for different hospital staff in Iran, especially those working in the emergency departments. In Reay et al study [22], emergency department nurses in Canada had high triage decision making, while in Tzeng et al study [23], majority of hospital nurses in Taiwan demonstrated poor readiness for disaster responses.…”
Section: Discussionmentioning
confidence: 97%
“…Houve prevalência do sexo feminino (81,5%). O tempo de formação apresentou mediana de 10 anos (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). A maioria dos participantes (118) possui um curso de pós-graduação (90,8%), sendo que 54 (45,8%) possui especialização, 41 (34,7%) mestrado e 18 (15,3%) doutorado.…”
Section: Resultsunclassified
“…3,7 Foi assinalado que os enfermeiros na triagem enfrentam um ambiente dinâmico e, para isso, necessitam de uma conduta flexível para classificar o risco de acordo com os recursos disponíveis durante o turno de trabalho. 8 No âmbito nacional, as pesquisas já realizadas têm destacado a avaliação da eficácia e qualidade da CR e seu impacto na dinâmica da organização dos serviços de urgência, 9 a confiabilidade e validade do protocolo de Manchester. 10 No entanto, há escassa literatura com foco no trabalho desenvolvido pelos enfermeiros na CR diante das dificuldades e vulnerabilidades desse posto de trabalho.…”
Section: Introductionunclassified
“…Triage is considered a dynamic and complex nursing activity that requires a high level of concentration in a work environment marked by frequent task interruptions, an unpredictable workload, and a noisy physical layout (79). These three elements may in uence the accuracy of the emergency levels that nurses assign to patients (32,52).…”
Section: Discussionmentioning
confidence: 99%